Animal Experiments in Homeopathic Research - Britton, Delny (Homœopathic Links, 2013)
Research into homeopathy is on the increase in response to calls for evidence of its effectiveness and mode of action. As such evidence grows, however, so too will questions about one of the methods researchers are using to add to our knowledge base: animal experiments. This article examines a controversial issue that many homeopaths are currently unaware of and presents scientific, political and ethical arguments as to why there is neither the need nor the justification for animal experimentation in homeopathic research. It also explains why its continued practice threatens homeopathyʼs reputation as an ethical profession, while doing little to advance its widespread acceptance.
Keywords: Homeopathy; Animal; Experiments; Ethics